A review data cube analysis method in big data environment - Ghazali, Dewi Puspa Suhana; Latip, Rohaya; Hussin, Masnida; Abd Wahab, Mohd Helmy (Asian Research Publishing Network, 2015)
With the development of computer technologies, the amount of data has explosive growth and the data volumes have approximately doubled each year. One of the tools that affect scalability and flexibility to handle structured as well as unstructured data called Hadoop. However, data cubes are widely used as a powerful tool to provide multi-dimensional views in data warehousing and On-Line Analytical Processing (OLAP). Therefore, it is becoming expensive to perform the data cube analysis when the data sizes increases. In this paper, we will investigate and review the methods of MapReduce in Hadoop.